Analysis of the Effect of Financing on the Profitability of Islamic Commercial Banking in 2016-2020 - Aguk Triyanto; Imam Mukhlis (Arkus, 2022)
This study was conducted to determine the effect of mudharabah, musyarakah, murabahah, and non-performing financing (NPF) financing on the profitability of sharia commercial banks registered with the Financial Services Authority (OJK) for the 2016-2020 period. The analysis used in this study uses vector error correction models (VECM) analysis techniques. The results of this study indicate that in the short term there is only one significant variable on return on assets (ROA), namely the NPF variable. Meanwhile, the results of the long-term analysis show that the mudharabah and NPF variables have a significant effect on ROA at the 5% level. Meanwhile, the musyarakah and murabahah variables have no significant effect on ROA. Meanwhile, the impulse response function (IRF) of the mudharabah, musyarakah and murabahah variables have a positive and negative effect, while the NPF variable has a negative effect. For FEVD the variable that has a major contribution to ROA is mudharabah financing, followed by murabahah and NPF, then the last contribution is the musyarakah variable.